The breadth and mnemonic consequences of the youth bias. Issue 7 (July 2016) - Koppel, Jonathan; Berntsen, Dorthe
We have recently demonstrated the existence of the youth bias, referring to a tendency to favour adolescence and early adulthood over other lifetime periods when making inferences about the timing of important public events across the lifespan of a typical individual within one's culture. The youth bias integrates two discrete lines of research, that is, the literature on the privileged status of adolescence and early adulthood in human memory and cognition, and the literature on cognitive biases. Here we first examined whether the youth bias holds for specific categories of public events (i.e., deaths of public figures, United States presidential elections, and sporting events). We then investigated the possible role of the youth bias in structuring recall for public events, by probing, within subjects, for the relation between: (1) these expectations of the timing, in a typical person's life, of the most important exemplar from each public event category, and (2) the age at which the cited event occurred on a recall question asking participants to cite the most important exemplar, in their own lifetime, from each category. We found a youth bias for each category. Additionally, responses to the youth bias question were correlated with the age at which the recalled event occurred, but only where particularly salient historical events did not play a central role in driving recall (i.e., for sporting events). We conclude that the youth bias holds across different types of public events and provides a default structure for organizing recall of public events.